The influence of metabolic syndrome in the outcomes of colorectal cancer patients - Goulart, André (2017)
Aims: Determine the influence of metabolic syndrome and its different components in the outcomes of colorectal cancer surgery at 30 days. Materials and methods: Prospective study that included all patients submitted to elective colorectal cancer surgery between August 2015 and August 2016 at Hospital de Braga. Clinical and laboratory parameters evaluated pre-operatively were: central obesity, blood pressure, fasting glucose, triglycerides levels and HDL cholesterol levels. Any complications during the first 30-days after surgery were recorded (readmission, reintervention, anastomotic dehiscence, morbimortality). Results: One hundred and thirty-four patients were included. Metabolic syndrome was diagnostic in 40.7% of patients with the ATPIII definition, 67.5% with the AHA definition and 67.0% with the IDF definition. At 30 days after colorectal cancer surgery, 73.1% patients don't have any complication, 15.7% have minor complications (grade I/II of Clavien-Dindo classification), 11.1% have major complications (grade III/IV/V of Clavien-Dindo classification) and 1.5% have died from surgical complications (grade V of Clavien-Dindo classification). The statistic analysis didn't reveal any association between MS, or it's different components, and surgical outcomes. Conclusion: This study seems to indicate that metabolic syndrome don't have any influence in surgical outcomes of colorectal cancer surgery. (C) 2017 Diabetes India. Published by Elsevier Ltd. All rights reserved.